Delayed diagnosis of traumatic ventricular septal perforation in penetrating chest injury: hematoma formation in the ventricular septum in CT suggests perforation. Issue 3 (25th April 2019) - Shioya, Nobuki; Inoue, Nozomu; Muto, Harutatsu; Tomita, Akiko; Tsukamoto, Yuki; Kawashima, Naonori; Hazama, Koji; Shichinohe, Yasuo
Abstract : Background: Ventricular septal perforation (VSP) can be caused by a penetrating cardiac injury. Diagnosis of VSP tends to be delayed because a shunt might not be detected by color flow Doppler at an early stage following injury. Case presentation: A 60‐year‐old man with depression was admitted to the emergency center after a knife injury in the chest. A focused assessment with sonography for trauma revealed cardiac tamponade. Shortly after an open cardiac massage and a pericardiotomy, his spontaneous circulation returned. At a later stage, follow‐up computed tomography, echocardiography, and left ventriculography showed traumatic ventricular septal perforation. Conservative therapy was chosen because the pulmonary blood flow/systemic blood flow ratio was 1.42. Conclusion: The initial contrast computed tomography shows a septal hematoma. Its presence could be perceived as a perforation site in the interventricular septum. Abstract : Ventricular septal perforation can be complicated by a penetrating cardiac injury. It has a tendency to present late because a shunt might not be detected by color flow Doppler at an early stage. The contrast computed tomography shows a septal hematoma; its presence could be a perforation of the interventricular septum.